2018
DOI: 10.1111/ejn.13991
|View full text |Cite
|
Sign up to set email alerts
|

Striatal alcohol cue‐reactivity is stronger in male than female problem drinkers

Abstract: Despite apparent sex differences in the development and treatment of alcohol use disorder, relatively little is known about the underlying neural mechanisms. In this study, we therefore investigated neural cue-reactivity in a sample of male (n = 28) and female (n = 27) problem drinkers (matched on age and alcohol use severity) with an average alcohol use disorder identification test score of 12 which is indicative of a likely alcohol use disorder. Neural cue-reactivity data were extracted from four regions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 62 publications
1
28
0
Order By: Relevance
“…Dovetailing with results in clinical samples, cue reactivity studies with social drinkers have also reported increases in attentional bias [223,224], heart rate variability [225], and craving [226][227][228] in response to alcohol cues in heavy drinkers. Interestingly, Roy-Charland et al [223] observed that participants who consumed more alcohol performed more frequent saccades into and out of alcohol-related image parts, a behavior reminiscent of sign-tracking.…”
Section: Findings In Alcohol Use Disorder and At-risk Populationsmentioning
confidence: 77%
See 1 more Smart Citation
“…Dovetailing with results in clinical samples, cue reactivity studies with social drinkers have also reported increases in attentional bias [223,224], heart rate variability [225], and craving [226][227][228] in response to alcohol cues in heavy drinkers. Interestingly, Roy-Charland et al [223] observed that participants who consumed more alcohol performed more frequent saccades into and out of alcohol-related image parts, a behavior reminiscent of sign-tracking.…”
Section: Findings In Alcohol Use Disorder and At-risk Populationsmentioning
confidence: 77%
“…Translation of animal research to humans remains, however, challenging, with less clear-cut findings than animal studies due, at least in part, to heterogeneity in the paradigms used, employed measures of conditioning (implicit physiological, explicit self-report or neuronal), level of awareness about the conditioning procedure and modifying factors, such as comorbidities, AUD severity and duration, or context (e.g., enrollment in treatment programs or recent detoxification). This notwithstanding, alcohol cues have been extensively proven to induce attentional and psychophysiological changes and increase craving in individuals with AUD [202][203][204][206][207][208][209][210][211][212][213][214][215], as well as social drinkers [223][224][225][226][227][228]. However, in contrast to animal research, conditioning of alcohol cues in human studies has usually taken place outside of the experimenter's control and is thus subject to an indeterminate number of potential confounders.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Clinical studies report that reduced insular grey matter volume is correlated with increased alcohol expectancy in female problem drinkers, but not in male problem drinkers (42). Interestingly, insular activation is further enhanced by alcohol cues in alcohol-dependent women compared to non-dependent women, while men show greater alcohol cue reactivity in the striatum compared to women (43,44). In light of these previous reports, the current experiment supports the notion that different neural circuits regulate alcohol drinking behaviors in males and females.…”
Section: Discussionmentioning
confidence: 99%
“…The bilateral dorsal striatum (DS) ROI was defined anatomically as the caudate and putamen from the Harvard‐Oxford atlas, also binarized at a 0.5 probability threshold. Overlap between the VS and DS regions was subtracted from the DS mask to distinguish between dorsal and VS areas (Kaag et al, 2019; Liu et al, 2017). Analyses of group differences in DS and VS cue reactivity, as well as associations between cue reactivity and behavioral measures, were conducted in R as general linear models.…”
Section: Methodsmentioning
confidence: 99%